2012
DOI: 10.3329/bsmmuj.v5i1.11033
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Voice

Abstract: When we age, not only our aches and pains worsen, our skin wrinkles, teeth fall out, and our hair disappears, voices show sign of age as well. Few of us just think about how important it is until it stops functioning properly. In advanced age, we loose some of the fine coordination that we had in younger years, we loose muscle mass, our mucous membrane become thin and dry. Aging affect two main aspects of vocal fold anatomy and function. First, much like muscles elsewhere in the body, muscles of the vocal fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
10
0
5
Order By: Relevance
“…This association encompasses chronic pharyngitis [ 11 ], obstructive sleep apnea [ 12 ], chronic rhinosinusitis [ 13 15 ], and asthma [ 16 ]. Furthermore, the awareness of LPR as an airway disease has grown [ 3 , 17 ]. However, one of the most common airway diseases in the world is allergic rhinitis (AR).…”
Section: Introductionmentioning
confidence: 99%
“…This association encompasses chronic pharyngitis [ 11 ], obstructive sleep apnea [ 12 ], chronic rhinosinusitis [ 13 15 ], and asthma [ 16 ]. Furthermore, the awareness of LPR as an airway disease has grown [ 3 , 17 ]. However, one of the most common airway diseases in the world is allergic rhinitis (AR).…”
Section: Introductionmentioning
confidence: 99%
“…Six hCS were more represented in older than in younger euthyroid subjects (p<0.01): periorbital puffiness, impairment of hearing, constipation, dry skin and diminished sweating and hoarseness of voice but these signs are also described in physiological aging (29-33). In SCH seniors, coarse skin and slow movements showed increased expression, correlated with high specificity and good positive LR.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious reason behind was that the singer in our study is a regular singer. It has been reported that voice of the professional singers take longer time to age, as they keep their laryngeal muscles strong by regular singing exercises [20]. The decrease in F0 in the later years of the singer may be related to hormonal effects observed in female singers.…”
Section: Fig 2 Average F0 Variations In the Singermentioning
confidence: 97%
“…The purpose of this study is to focus on the effect of aging collectively on large number of singing voice parameters. Firstly it is observed that most of the aging analysis has been performed on speakers, either for sustained vowels, reading passages or recorded materials for speech related features like speech rate, sound pressure level, F0, F0 range, vowel formants, voice range profile, tremor or shakiness in the voice [1,12,[17][18][19][20][21]. But singing is different from speaking.…”
mentioning
confidence: 99%